4D printing of thermoresponsive OEGMA-based hydrogels with tunable response [data] - Tran, Hoang Bao Duc; Spiegel, Christoph A.; Blasco, Eva (Universität, 2025)
Hydrogels, particularly those exhibiting responsive behaviors, have gained significant attention, especially with the advent of 4D printing. Among thermoresponsive hydrogels, poly(N-isopropylacrylamide) (PNIPAM)-based materials remain a benchmark for 4D microprinting featuring typical lower critical solution temperatures (LCSTs) ranging from 32 to 37 °C. However, precise tuning of the LCST to a broader temperature range is necessary to expand the application window. This study introduces thermoresponsive poly(oligo(ethylene glycol)methacrylate) (POEGMA)-based polymers as alternative printable materials for two-photon laser printing (2PLP). First, a library of prepolymers with LCSTs ranging from 33 to 66 °C is synthesized and characterized. By formulating these prepolymers with a suitable photoinitiator in water, inks compatible with 2PLP are created. The printing performance of each ink is evaluated by fabricating complex 4D microstructures, including various platonic solids exhibiting LCSTs ranging from 33 to 66 °C, surpassing the constraints of PNIPAM. The actuation performance of each material is evaluated quantitatively by monitoring volume changes at different temperatures. Finally, arrays of “twistable” tetrahedrons are fabricated in multi-material fashion, showcasing temperature selective actuation. Thus, we demonstrate that the careful design of the macromolecular architecture offers precise LCST adjustment in final printed microstructures, a feature highly beneficial for applications like soft microrobotics among others.
Gefördert durch: Deutsche Forschungsgesellschaft (DFG): SPP 2206 - DFG Priority program “Cooperative Multistage Multistable Microactuator Systems”: BL1604/5-2; Excellence Cluster “3D Matter Made to Order”: EXC-2082/1-390761711; Carl-Zeiss-Foundation: FocusHEiKA
Gesehen am 10.04.2025
Keywords: Forschungsdaten; Datenbank